Pengaruh Word Of Mouth dan Brand Image Terhadap Keputusan Pembelian Dalam Prespektif Bisnis Islam : Studi Pada Mie Gacoan Cabang Diponegoro Bandar Lampung - Fatih Fuadi; Heni Verawati; Inka Corlita (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
Purchasing decisions are a very important factor in the culinary business. When choosing food, consumers definitely look at several factors such as recommendations from other people and the brand image of the food. If consumers get positive recommendations from other people and also have a good brand image, this can encourage consumers to make purchasing decisions. The formulation of the problem in this research is, do Word of Mouth and Brand Image influence the decision to purchase Mie Gacoan at the Diponegoro Bandar Lampung branch? What is the influence of Word of Mouth and Brand Image on purchasing decisions for the Diponegoro branch of Mie Gacoan which is studied from an Islamic business perspective. The aim of this research is to determine the influence of Word of Mouth and Brand Image on purchasing decisions for Mie Gacoan at the Diponegoro Bandar Lampung branch. And also viewed from an Islamic business perspective. This research is a quantitative research, the population in this research is consumers of Mie Gacoan, Diponegoro Bandar Lampung branch. The sample used in this research was 96 people who had bought Mie Gacoan at the Diponegoro Bandar Lampung branch. Sampling used purposive sampling. Data collection uses questionnaires and interviews. The data analysis technique used in this research is the SEM model using SmartPLS version 4.0. The results of this research are that Word of Mouth has a positive and significant effect on purchasing decisions for Mie Gacoan at the Diponegoro Bandar Lampung branch. Brand Image has a positive and insignificant effect on purchasing decisions for Mie Gacoan at the Diponegoro Bandar Lampung branch. Islamic teachings do not prohibit humans from fulfilling their needs or desires, as long as with this fulfillment, human dignity can increase. Everything on this earth was created for the benefit of humans, but humans are commanded to consume goods/services that are halal and appropriate in moderation, not excessively. Fulfilling needs or desires is still permitted as long as it can add to the benefit or does not bring harm.